Mapeamento de uso e cobertura da terra e levantamento florístico e fitossociológico em fragmento de vegetação nativa na Guarnição de Aeronáutica de Pirassununga-SP - Queiroz, Israel Henrique Buttner (2024)
The native vegetation of São Paulo is highly fragmented in different sizes, many of which still have no biological record. The Aeronautics Garrison of Pirassununga (GUARNAE-YS) has about 2000 hectares (ha) of remnants of cerrado vegetation, Riparian Forest and transition areas. Remote sensing assists in mapping vegetation and land use and cover changes (UCT). Besides the reduction of the areas of Cerrado sensu lato, there was the conversion of more open to more closed phytophysiognomies. In this context, phytosociological research is fundamental to verify floristic and structural changes in vegetation over time. The objective of this dissertation was to study the cerrado vegetation in the GUARNAE-YS, through the analysis of the UCT, floristic survey and phytosociological analysis. The objective of the first chapter was to recognize the UCT classes of the GUARNAE-YS and evaluate the accuracy of the classification of the MapBiomas project of 1985 and 2021 with pixels of 30 and 10 m. MapBiomas data were edited manually through the visual interpretation of satellite images for quantify pixels with errors of omission and commission, in addition to evaluating changes in CTU. In the analyzed period, there was a reduction of the Savanna Formation and the Mosaic of Uses, while the Forest Formation increased. The highest proportion classes were the Mosaic of Uses occupying almost half of the entire area followed by the Forest Formation, which was the largest among the areas of native vegetation. The Kappa index in the analyzed mappings indicate a very good agreement. The second chapter aimed to carry out a preliminary survey of trees in two forest fragments of the GUARNAE-YS, the transition between Cerradão and Seasonal Semideciduous Forest (FES) containing a patch of Cerrado sensu stricto (s.s.), and another fragment of FES associated with the Riparian Forest. Through random collections, 47 families and 125 species were recognized, of which 82 species have traditional Brazilian use and six are under some degree of threat, an invasive species that requires attention was also recognized. The aim of the third chapter was to describe the floristic, phytosociological and structural composition of the Cerrado sensu stricto (s.s.) of the GUARNAE-YS. The phytosociological census was performed with the inclusion criterion D30 5 cm and calculated the phytosociological parameters and diameter distribution and height of the individuals. Forty species from 24 families were identified, below the value of the other studies. There is dominance of few species in the community highlighting the family Fabaceae by the richness in species and community structure. In the absence of fires, the vegetation became almost all forest except where there is military training indicating that this action delayed the density. Species intolerant to the shaded environment were recognized, and their permanence in the vegetation depends on the heterogeneous environment of the Cerrado s.s. The structural aspects of the the recognized species and the history of the site allow to affirm that the Cerrado s.s. patch studied is an encrave in the middle of the transition fragment between Cerradão and FES. The results of this dissertation highlight the potential of the GUARNAE-YS to the conservation of biodiversity in the Mogi Guaçu River Basin.